La justicia restaurativa y su incidencia en la reinserción social de los jóvenes en conflicto con la Ley Penal del Programa IV del Centro Juvenil de Diagnóstico y Rehabilitación de Lima - Garcia Leon, Jannet Jackelyne (2021)
The objective of this research work is to examine the way in which a proper application of restorative juvenile criminal justice in the Juvenile Diagnosis and Rehabilitation Center of Lima affects the reintegration of young people in conflict with the Criminal Law, especially to demonstrate the Inconsistencies in the Juvenile Mediation Protocol approved and in force to date, in order to find better legal treatment in compliance with the primary objectives, when there is a socio-educational measure of internment, such as resocialization and reincorporation of said young people to the society. Likewise, it is associated with other specialties such as family law and alternative means of dispute resolution. As part of the study, we will use scientific research techniques and tools such as the survey, the analysis of books, norms and legal standards. We have found that mediation with the restorative justice approach would achieve its objectives as there is currently the interest of young people in conflict with the Penal Law of Program IV of the Juvenile Diagnosis and Rehabilitation Center of Lima in participating in this restorative practice. Finally, to strengthen the Restorative Justice program, we present the modifications to the Juvenile Criminal Mediation Protocol, mainly the internment measure, which will be adjusted to the needs that ensure both young people in conflict with the Criminal Law, as well as that of the authorities. who are available to assist in its production, thus achieving such important effects of forgiveness, mutual satisfaction, and resocializing effects for young people, making them understand the consequences of their actions, but also the possibility of successfully reincorporating to society through the forgiveness and empathy of the victim, the young person and society.